Hyperalgesia induced by Asp49 and Lys49 phospholipases A2 from Bothrops asper snake venom: pharmacological mediation and molecular determinants - Chacur, Marucia (2003)
The ability of Lys49 and Asp49 phospholipases A2 (PLA2), from Bothrops asper snake venom, to cause hyperalgesia was investigated in rats, using the paw pressure test. Intraplantar injection of both toxins (5–20 μg/paw) caused hyperalgesia, which peaked 1 h after injections. Incubation of both proteins with heparin, prior to their injection, partially reduced this response. Chemical modification of Asp49 PLA2 with p-bromophenacyl bromide (p-BPB), which abrogates its PLA2 activity, also abolished hyperalgesia. Intraplantar injection of a synthetic peptide corresponding to the C-terminal sequence 115–129 of Lys49 PLA2, caused hyperalgesia of similar time course, but varying magnitude, than that induced by the native protein. In contrast, a homologous peptide derived from the Asp49 PLA2 did not show any nociceptive effect. Hyperalgesia induced by both PLA2s was blocked by the histamine and serotonin receptor antagonists promethazine and methysergide, respectively, by the bradykinin B2 receptor antagonist HOE 140 and by antibodies to tumor necrosis factor alfa (TNFα) and interleukin 1 (IL-1). Pretreatment with guanethidine, atenolol, prazosin and yohimbine, inhibitors of sympathomimetic amines, or with indomethacin, inhibitor of the cyclo-oxygenase pathway, reduced Lys49 PLA2-induced hyperalgesia without interfering with the nociceptive activity of Asp49 PLA2. The hyperalgesic response to both myotoxins was not modified by pretreatment with celecoxib, an inhibitor of the cyclo-oxygenase type II, by zileuton, an inhibitor of the lipoxygenase pathway or by Ng-methyl-l-arginine (LNMMA), an inhibitor of nitric oxide synthase. These results suggest that Asp49 and Lys49 PLA2s are important hyperalgesic components of B. asper venom, and that Lys49 and Asp49 PLA2s exert their algogenic actions through different molecular mechanisms.